Removal of phosphorus from aqueous solutions using selected materials - Tiong, Pei Jen. (Universiti Malaysia Sarawak, (UNIMAS), 2007)
In Malaysia, eutrophication induced by excess phosphorus in water sources is one of the major causes of water polution. The sources of phosphorus include grey water and the inefficiently treated effluents from septic tanks.